COMPARISON OF POSTOPERATIVE PAIN SCORES AND MEDICATION USAGE BETWEEN THREE PAIN CONTROL STRATEGIES FOR PEDIATRIC ANTERIOR CRUCIATE LIGAMENT (ACL) SURGERY. Issue 3 (31st March 2019) - Lovejoy, John F.; Santana, Lisgelia; Atanda, Alfred; Mandel, David; Day, Jason; Kiebzak, Gary M.
Background: Assessment and management of postoperative pain in the pediatric population after ACL surgery can be challenging, and the optimal approach to pain control remains controversial. Recent studies have shown that the use of intraoperative nerve blocks may reduce the need for opioids to control pain in the immediate postoperative period. However, it is not clear which block type is the most beneficial for the pediatric outpatient setting. The objective of our study was to compare effectiveness of pain control between three different pain management strategies in the pediatric ACL population. Methods: A retrospective chart review from 2013-2017 of patients ages 12-17 receiving an elective ACL reconstruction. Three types of analgesia were included: femoral nerve block, combined femoral + sciatic block, and intraarticular injection of bupivacaine with cold therapy in the Post Anesthesia Care Unit (PACU) (each used by three different surgeons as their standard preference in three different hospitals), n = 50 per group. The primary variable was postoperative pain scores (visual analog scale 1-10) in the PACU. Secondary variables collected were demographic data, graft type, time in PACU and intraoperative/postoperative opioid use. Results: The mean (+ SD) age of the cohort was 15.3 + 1.4 years; there were no differences in age, BMI or ratio of boys and girls between the 3 groups (n=50 per group). However, the femoral nerve block group had a significantly lower percentage of Caucasians (28%, P = 0.002) compared to the group with combined blocks (58%) and intraarticular injection (56%). Less than 50% of patients in the combined nerve block group had opioids intraoperatively or in the PACU compared to nearly 100% of patients in the other two groups (P < 0.0001). Also, for patients receiving opioids, the total intraoperative morphine equivalents and PACU pain scores (all patients) were significantly less in the combined block group (P < 0.001). For patients receiving opioids in the PACU, the total morphine equivalents was significantly higher in the intraarticular injection group compared to the nerve block groups (P < 0.0001). Total time in the PACU was 25% longer for patients in the combined block group (P < 0.0001). Conclusion: Patients in the combined femoral and sciatic nerve block group had significantly better pain scores in the PACU with less cumulative morphine equivalent consumption compared to the femoral nerve block group and the intraarticular injection group.